Ignacy Chrzanowski w relacjach słuchaczy = Students on Ignacy Chrzanowski - Łojek, Mieczysław (1930-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This paper treats of Ignacy Chrzanowski, the outstanding Polish scholar who was professor of the Jagellonian University from 1910 to 1939. The considerations concentrate on two thematic spheres: in the first one the professor is shown as a paragon of an academic educator. The second one treats of the style of his scientific work revealed in lectures and publications.
Keywords: Chrzanowski, Ignacy (1910-1939)